The Construction of a Term Database to Support the Compilation of Chinese-Slovene Slovene-Chinese Dictionary of Beekeeping Terms - Anže SOBOČAN (Acta Linguistica Asiatica, 2014)
This paper introduces the first step of making a multilingual specialized dictionary, which includes a selection of terms, their arrangement according to adequacy and the determination of synonymous relationships between the terms. The research was based of the first phase of compiling a Slovene-Chinese and Chinese-Slovene specialized beekeeping dictionary. The results of the research could, however, be applied to the making of specialized dictionaries for any research field. The focus areas of the paper are: the partial overlapping of everyday language and specialized terminology; the different arrangement approaches of existing dictionaries; the many synonyms that are often wrongly understood to denote different things; the coining of new terms when needed; the traps of literal translation.